Kesan intervensi kelompok pendekatan psiko realiti terhadap tingkah laku agresif dalam kalangan remaja sekolah menengah - Suhaila, Abdullah (2017)
Recently, the issue of aggressive behaviour has been overwhelming. This can be seen from statistical data on school misconduct that increasingly every year which involved cases such as quarrels, vandalism and rudeness toward teachers. Therefore, the objective of this study was to identify the effects of the Module of Psycho Reality Approach Group Intervention on the level of aggressive behavior (physical, verbal, emotional, hostile) among adolescence in secondary school. This study used an experimental quasi design that invoIves two groups which are the treatment group and the control group. Subjects of this study consist of eighty students. The treatment group was given the intervention known as a Psycho Reality Approach Group whereas the control group did not received any intervention. The Aggressive Questionnaire (AQ) was given to the subjects of both groups at pretest, posttest one and posttest two to measure the level of students' aggression. The data were using Hestand SPA NOVA test. The findings have shown that the treatment group had received a positive effect after the intervention compared to the control group. The findings revealed that the level of students' aggression had decreased in the treatment group. Hence, this study do have significant contribution to school in preventing aggressive behaviour among school adolesence.